2019
DOI: 10.1055/a-1023-7419
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction of Pyrrolizidine Alkaloids from Plants by Pressurised Liquid Extraction – A Preliminary Study

Abstract: Pyrrolizidine alkaloids and their corresponding pyrrolizidine alkaloid-N-oxides are secondary plant constituents that became the subject of public concern due to their hepatotoxic, pneumotoxic, genotoxic, and cytotoxic effects. In contrast to the well-established analytical separation and detection methods, only a few studies have investigated the extraction of pyrrolizidine alkaloids/pyrrolizidine alkaloid-N-oxides from plant material. In this study, we have applied pressurized liquid extraction with the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…7 The levels of intermedine and lycopsamine in a German root specimen varied between 0.218 and 0.483 mg/g and 0.096 and 0.249 mg/g, respectively, depending on the extraction temperature (50-125 C) and additive (phosphoric acid, ammonia, sulfuric acid, acetic acid, formic acid) included in the aqueous extraction solvent. 33 The same two PA markers were quantified by Avula et al, 24 with their levels up to maximum 0.015 mg/g. Liu et al 26 showed that lycopsamine levels in a Colombian comfrey root specimen were between 0.010 and 0.014 mg/g in a pressurized hot water extract and between 0.029 and 0.032 mg/g in a methanol/water (1/1) extract obtained under reflux.…”
Section: Lc-hrms/ms Profiling Of Phenolic Markersmentioning
confidence: 89%
“…7 The levels of intermedine and lycopsamine in a German root specimen varied between 0.218 and 0.483 mg/g and 0.096 and 0.249 mg/g, respectively, depending on the extraction temperature (50-125 C) and additive (phosphoric acid, ammonia, sulfuric acid, acetic acid, formic acid) included in the aqueous extraction solvent. 33 The same two PA markers were quantified by Avula et al, 24 with their levels up to maximum 0.015 mg/g. Liu et al 26 showed that lycopsamine levels in a Colombian comfrey root specimen were between 0.010 and 0.014 mg/g in a pressurized hot water extract and between 0.029 and 0.032 mg/g in a methanol/water (1/1) extract obtained under reflux.…”
Section: Lc-hrms/ms Profiling Of Phenolic Markersmentioning
confidence: 89%
“…35 Pyrrolizidine alkaloids have also been identified in Senecio jacobaea and Senecio Brasiliensis species, where their anti-inflammatory, immunomodulatory and cytotoxic effect have been demonstrated. 36,37 In the case of Senecio nulans, Senecio chiquianensis, Senecio hyoseridifolius, Senecio tphrosiodies, secondary metabolites have been identified in ethanolic extracts and essential oils (terpenes, phenolic compounds, flavonoids, pyrrolizidinic alkaloids, lactones), showing good antibacterial activity against staphylococcus aureus bacteria. [38][39][40][41] It is necessary to explore the characterization of secondary metabolites of Senecio rhizomatus in order to guide in vitro and in vivo pharmacological research that would favor the preservation and rational use of the species.…”
Section: Discussionmentioning
confidence: 99%
“…As well as, Nedelcheva et al (2015) also identified two PAs named, seneciphylline (129) and integerrimine (128) by gas chromatography and mass spectrometry analysis ( Nedelcheva et al , 2015 ). Senecivernine (130) was quantified by HPLC-MS/MS and pressurised liquid extraction ( Kopp et al , 2020 ). The authors concluded that this approach can be used to the complete and automated extraction of pyrrolizidine alkaloids ( Kopp et al , 2020 ).…”
Section: Phytochemical Aspectmentioning
confidence: 99%
“…Senecivernine (130) was quantified by HPLC-MS/MS and pressurised liquid extraction ( Kopp et al , 2020 ). The authors concluded that this approach can be used to the complete and automated extraction of pyrrolizidine alkaloids ( Kopp et al , 2020 ). Tussilagine (121), another PAs, has been isolated and identified in flowers of coltsfoot by HILIC/ESI-QTOF-MS and HPTLC ( Smyrska-Wieleba et al , 2017 ).…”
Section: Phytochemical Aspectmentioning
confidence: 99%
See 1 more Smart Citation